The influence of observers on children’s conformity in moral judgment behavior - Lee, Yoonha; Song, Hyun-joo (Frontiers in Psychology, 2024)
Children autonomously make sound moral judgments based on internal criteria, but they tend to make erroneous judgments in the presence of social influences, and the reasons for these errors are not well understood. Thus, the current research investigated how the presence of observers who can see and listen to 3-year-old children’s judgments but who do not present their opinions influences children’s conformity in moral judgment behavior. In Experiment 1, the children (N = 30) were presented with pictures depicting prosocial behaviors and asked whether the behaviors were acceptable. The children’s tendency to change their answers after hearing the counterintuitive opinions of informants was then measured. The results showed that the children’s moral judgments were more likely to conform to that of the group in the presence of observers. Experiment 2 aimed to determine the reason children were more likely to conform to a group when being watched by observers in Experiment 1. Children (N = 30) were randomly assigned to two conditions with different observer conditions as follows. Observers were either wearing headsets, indicating that they could not hear the children’s responses, or had them hanging around their necks, indicating that they could. The results showed that children’s conformity behavior depended on whether observers could hear what they were saying. The current findings are expected to help elucidate not only social factors that affect children’s moral judgments but also the developmental mechanism of an observer effect.